Natural gas engineering handbook - Guo, Boyun (Gulf Pub. Company, 2012)
The demand for energy consumption is increasing rapidly. To avoid the impending energy crunch, more producers are switching from oil to natural gas. While natural gas engineering is well documented through many sources, the computer applications that provide a crucial role in engineering design and analysis are not well published, and emerging technologies, such as shale gas drilling, are generating more advanced applications for engineers to utilize on the job. To keep producers updated, Boyun Guo and Ali Ghalambor have enhanced their best-selling manual, Natural Gas Engineering Handbook, to continue to provide upcoming and practicing engineers the full scope of natural gas engineering with a computer-assisted approach. This must-have handbook includes: A focus on real-world essentials rather than theoryIllustrative examples throughout the textWorking spreadsheet programs for all the engineering calculations on a free and easy to use companion siteExercise problems at the end of every chapter, including newly added questions utilizing the spreadsheet programsExpanded sections covering today's technologies, such as multi-fractured horizontal wells and shale gas wells.
Keywords: Natural gas -- Handbooks, manuals, etc.; Petroleum engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books